A holistic solution for the analysis of excavation and specialist data in a 3D GIS framework - Campbell , Rosie; Boyd , Michael J.; Herbst , James; Indgjerd , Hallvard R.; Meyer , Nathan; Renfrew , Colin (Journal of Greek Archaeology, 2024)
This paper seeks to summarise the development and showcase the uses of a 3D GIS-based tool used by the Keros Project in our work at the Early Bronze Age site of Dhaskalio, Keros. While reflexivity and born-digital tools were built into the design of the 2016-2018 excavations, the issue of how appropriately to use, analyse and make accessible the vast quantities of digital data, especially the over one thousand 3D SFM photogrammetric models, came to the forefront of the post-excavation programme. This tool aims to be a ‘one-stop shop’ for the interpretation of the excavation, including multi-layered 3D views of the site and all geo-located data resulting both from the excavation and from subsequent specialist studies. This is a true 3D GIS system, encapsulating all the abilities of a traditional GIS, including data entry, database management, data analysis and manipulation, while giving access to all excavation and specialist data within a single platform, making the tool data- driven and research-oriented.